The Role of Lithospheric Flexure in the Landscape Evolution of the Wilkes Subglacial Basin and Transantarctic Mountains, East Antarctica. Issue 3 (19th March 2019) - Paxman, Guy J. G.; Jamieson, Stewart S. R.; Ferraccioli, Fausto; Bentley, Michael J.; Ross, Neil; Watts, Anthony B.; Leitchenkov, German; Armadillo, Egidio; Young, Duncan A.
Abstract: Reconstructions of the bedrock topography of Antarctica since the Eocene‐Oligocene Boundary (approximately 34 Ma) provide important constraints for modeling Antarctic ice sheet evolution. This is particularly important in regions where the bedrock lies below sea level, since in these sectors the overlying ice sheet is thought to be most susceptible to past and future change. Here we use 3‐D flexural modeling to reconstruct the evolution of the topography of the Wilkes Subglacial Basin (WSB) and Transantarctic Mountains (TAM) in East Antarctica. We estimate the spatial distribution of glacial erosion beneath the East Antarctic Ice Sheet, and restore this material to the topography, which is also adjusted for associated flexural isostatic responses. We independently constrain our post‐34 Ma erosion estimates using offshore sediment stratigraphy interpretations. Our reconstructions provide a better‐defined topographic boundary condition for modeling early East Antarctic Ice Sheet history. We show that the majority of glacial erosion and landscape evolution occurred prior to 14 Ma, which we interpret to reflect more dynamic and erosive early ice sheet behavior. In addition, we use closely spaced 2‐D flexural models to test previously proposed hypotheses for a flexural origin of the TAM and WSB. The pre‐34 Ma topography shows lateral variations along the length of the TAM and WSB that cannot be explained by uniform flexure along the front of the TAM. We show that some of these variations may be explained by additional flexural uplift along the south‐western flank of the WSB and the Rennick Graben in northern Victoria Land. Key Points: We present Oligocene–Pliocene reconstructions of the bedrock topography of the Wilkes Subglacial Basin and Transantarctic Mountains Preglacial landscape of the Wilkes Subglacial Basin was situated close to sea level and governed in part by flexure and crustal structure Dynamic and oscillatory Oligocene–Miocene ice sheets drove enhanced bedrock erosion and associated flexural isostatic uplift